Pengaruh Latihan Fundamental Movement Skills (FMS) pada Anak dengan Gangguan Koordinasi Perkembangan (Dyspraxia) - Ahmad Yani; Ibnu Sina (Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2022)
The background of this research is the phenomenon of lack of fundamental movement skills (FMS) in children with developmental coordination disorders (dyspraxia). The purpose of this study was to examine the effect of the Fundamental Movement Skill (FMS) exercise model on improving the ability of Fundamental Movement Skills (FMS) in children with dyspraxia. A total of 10 children voluntarily and with parental consent were assigned to the experimental group (DYS) [exp], who received 6 weeks of FMS training. FMS was assessed using the Test of Gross Motor Development-2. The method in this study used pre-experimental research methods. The design used in this research is The one group pretest-posttest design. The results of the study show that the fundamental movement skill (FMS) exercise model has an effect on the ability of the fundamental movement skill (FMS). It is evident from the results of the pretest research data analysis that the average value of the Movement Skill (FMS) fundamental movement exercise obtained is 13.23, while the posttest result of the average value of the Movement Skill (FMS) fundamental movement exercise obtained is 23.13, meaning that there is a Theincrease obtained after doing the Fundamental Movement Skill (FMS) exercise so that this shows a significant influence from the Movement Skill (FMS) fundamental movement training model on the Movement Skill (FMS) fundamental movement ability in children with dyspraxia. Thus, it can be concluded that the Fundamental Movement Skill (FMS) exercise model has a significant effect on increasing the Fundamental Movement Skill (FMS) ability of children with developmental coordination disorders (dyspraxia). The theoretical implication of this research is that the FMS training model can be a theoretical reference and knowledge reference for adaptive physical education teachers who teach in special schools in carrying out learning related to dyspraxia and the practical implications of the results of this study can be used by teachers, especially education teachers. adaptive physics as an exercise model to improve FMS in students with dyspraxia.